Study of Some Fenugreek (Trigonella foenum-graecum L.) Components and Effect of Their Extracts on Liver Enzymes and Growth of Some Microorganisms (Journal of the College of Basic Education, 2022)
The chemical components of the Trigonella leaves in the watery and alcoholic extracts were identified .The results showed that the extract contain : glycosides , saponins ,tannins ,phenolic compounds , resins ,alkaloids and flavonoids . The results also showed that there were high concentrations of K , Na , Ca with (171.2 , 19 , 18.3) ppm, respectively and low concentrations of Fe, Zn ,Cu, Mg with (5.1, 3.2 ,2.3 ,1.9) ppm, respectively ,very low concentrations Cr ,Cd , Pb with (0.9 ,0.7, 0.2) ppm The effects of these extracts on the liver enzymes and found Inhibition AST, ALT and effects of these extracts on the growth of different bacteria were studied, has been found that 0.5 mg/ml concentration was effective inhibitor of growth of Proteus mirabilis ,E.coli and Staphylocoous aureus